Metastatic brain tumours in Pakistan: An epidemiological overview - Muhammad Usman Khalid; Mashal Murad Shah; Mohammad Hamza Bajwa; Syed Nabeel Zafar; Altaf Ali Laghari; Saad bin Anis; Muhammad Faraz Raghib; Naveed Zaman Akhunzada; Sameen Siddiqi; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
Objective: To quantify the metastatic brain tumour burden presenting to tertiary care neurosurgical centres, the demographics and mortality rate, and the type of metastatic tumours commonly presenting to neurosurgical practice. Methods: A cross-section retrospective study was conducted on patients diagnosed with brain tumours from 32 neurosurgical centres across Pakistan between January 1, 2019, to December 31, 2019. At least one neurosurgical resident and one neurosurgical faculty member were recruited from each centre as members of the Pakistan Brain tumour consortium. Mean with standard deviation or median with interquartile range was reported as variables. Results: Of 2750 patients in this cohort, 77 (2.8%) were diagnosed with metastatic brain tumours. The median age of these patients was 52 (IQR= 43-60) years; 9 (14%) adults were aged 20-39 years, 37 (57%) were aged 40-59, and 19 (29%) were aged 60 and above. There were 62 (82.7%) married patients with 4% unmarried. The median KPS score both pre and post-surgery was 80 (IQR= 60-90, 70-90 respectively), and 43 (55.8%) patients were lost to follow-up. The mortality rate for patients that followed up was 50%, 17 patients were alive, and 17 were deceased at the end of the study period. The 30-day mortality rate amongst our patients was 11.8% (n=4). Conclusion: The number of patients presenting to neurosurgical care with brain metastases is much lower than the expected incidence of metastatic brain lesions. Multidisciplinary integration and the establishment of a registry to track patients diagnosed with brain tumours is the first step in ensuring better care for these patients. Keywords: Brain Metastases, Epidemiology, LMIC, Neuro-oncological surgery, Continue....